PENERAPAN MODEL GUIDED DISCOVERY LEARNING PADA MATERI PELUANG DI SMA NEGERI 02 SUNGAI RAYA - Nur aini Nur aini; Edy Yusmin; Ahmad Yani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis reseach aims to determine the effectiveness of the application of the Guided Discovery Learning model in probability material in grade XII SMAN 02 Sungai Raya. The method in this reseach is an experimental method, the type of research used is a pre-experimental design with one shot case study design. The subject used was students grade XII IPA 3 in SMAN 02 Sungai Raya. Data collection techniques used are measurement techniques and direct observation techniques. Data collection tools used in the form of tests of problem solving abilities and observation sheets of learning activities of students. Based on the results of the reseach, the feasibility of learning using the Guided Discovery Learning model in learning conducted during the two meetings is quite good, amounting to 3.16. Learning activities of students while using the Guided Discovery Learning model are classified as active, amounting to 69.9%. The problem solving abilities of students who are given learning using the Guided Discovery Learning model are still classified as moderate because only 80% of students reach KKM which is 76. The application of the Guided Discovery Learning model to the probability material in grade XII of SMAN 02 Sungai Raya is not effective. Keyword: Model Guided Discovery Learning, Probability